MANAGEMENT OF THE OIL AND GAS INDUSTRY IN INDONESIA MANAGERIAL PERSPECTIVE (STUDY IN THE INDONESIAN UPSTREAM OIL AND GAS INDUSTRY) - Arifin, Kasman; Hidayat, Dina; Maulana Arifin, Iqbal (Dinasti Publisher, 2021)
This article discusses the organization of upstream oil and gas industri in Indonesia from managerial perspective. For Indonesian context, actually this has been arranged by the Statement Oil and Gas Standard Accountancy No.29 Year 2009. In developed countries such as United States there is Standard Financial Accounting Statement issued by Financial Accounting Standard Board (FASB). In order to obtain clarity and transparency and to avoid different interpretation between the contractors and the government, therefore there ought to be explicit principles and methods in production sharing contract and desired accountancy period so that the similar method can be applied on APBN (National Planning and Expenditure Budget). This is since accountancy method affects financial report. With the latter, contractor’s performance and state income can be measured. Research methodology are ground research and exploratory research, reaseacher assumption based on field condition and resolve problem from literature study.